Hayabusa2 pinpoint touchdown near the artificial crater on Ryugu: Trajectory design and guidance performance. Issue 8 (15th October 2021) - Kikuchi, Shota; Saiki, Takanao; Takei, Yuto; Terui, Fuyuto; Ogawa, Naoko; Mimasu, Yuya; Ono, Go; Yoshikawa, Kent; Sawada, Hirotaka; Takeuchi, Hiroshi; Ikeda, Hitoshi; Fujii, Atsushi; et al.
Abstract: One of the major challenges in the Hayabusa2 sample-return mission was the second touchdown on the asteroid Ryugu, which was designed to collect subsurface materials near the artificial crater formed by a small carry-on impactor. Due to engineering and scientific requirements, a narrow area with a radius as small as 3.5 m was selected as the target landing site. To achieve pinpoint touchdown at the selected site, an artificial landmark called a target marker (TM) was used for optical navigation. The key to a successful touchdown was precise deployment of the TM in the microgravity environment of the asteroid. This study therefore investigates a viable trajectory for TM deployment, incorporating the uncertainty in the impact and rebound motions of the TM. Following the TM deployment operation, a detailed survey of the landing site around the TM settlement point is performed to assess the terrain conditions. To guarantee the observation quality and spacecraft safety, multi-impulse low-altitude trajectories are introduced in this paper, along with covariance analyses based on the high-fidelity polyhedral gravity model of Ryugu. Subsequently, a pinpoint touchdown trajectory that satisfies various engineering requirements, such as landing accuracy and velocity, is designed, taking advantage of optical TM tracking. The feasibility of the touchdown sequence is further validated by a Monte Carlo dispersion analysis. Consequently, Hayabusa2 successfully touched down within the target site on 11 July 2019. The current research also conducts a post-operation trajectory reconstruction based on the flight data to demonstrate the actual guidance performance in the TM deployment, landing site observations, and pinpoint touchdown.